Detection of Neospora caninum IgG Antibodies in Goats in Elazig, Erzurum and Kirsehir Provinces of Turkey - Utuk, A. E.; Simsek, S.; Piskin, F. C.; Balkaya, I (Israel Veterinary Medical Assoc, 2011)
The aim of this study was to detect Neospora caninum IgG antibodies in Saanen and Hair goats from Elazig, Erzurum and Kirsehir provinces of Turkey. For this, a total of 128 sera obtained from goats were tested using a commercially available competitive enzyme-linked immunosorbent assay (c-ELISA) kit. Overall prevalence of anti-N.caninum antibodies was 10.2% (13/128); and mean prevalence in Hair and Saanen goats were 13.8% (12/87) and 2.4% (1/41) respectively:This is the first serological study on caprine neosporosis in the above mentioned provinces of Turkey.
Keywords: Neospora caninum; goat; c-ELISA; Turkey